2020
DOI: 10.3389/fmicb.2020.00090
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Damage and Cancer-Associated Biomarkers in Helicobacter pylori-Infected Children

Abstract: Helicobacter pylori (H. pylori) is well-known to be involved in gastric carcinogenesis, associated with deregulation of cell proliferation and epigenetic changes in cancerrelated genes. H. pylori infection is largely acquired during childhood, persisting long-term in about half of infected individuals, a subset of whom will go on to develop peptic ulcer disease and eventually gastric cancer, however, the sequence of events leading to disease is not completely understood. Knowledge on carcinogenesis and gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 192 publications
(230 reference statements)
0
23
0
1
Order By: Relevance
“…Conversely, to the inflammatory model, more recent findings demonstrate that several tumor suppressor genes are consistently downregulated among children diagnosed with H. pylori [24,25]. This finding suggests there may be other potential pathways in which H. pylori infection can cause malignancy, emphasizing the greater motivation for continued follow-up, screenings, and/or treatment of infected children.…”
Section: H Pylori Infection and Gastric Cancermentioning
confidence: 99%
“…Conversely, to the inflammatory model, more recent findings demonstrate that several tumor suppressor genes are consistently downregulated among children diagnosed with H. pylori [24,25]. This finding suggests there may be other potential pathways in which H. pylori infection can cause malignancy, emphasizing the greater motivation for continued follow-up, screenings, and/or treatment of infected children.…”
Section: H Pylori Infection and Gastric Cancermentioning
confidence: 99%
“…To reveal how the DMGs impact their expression levels is one of our future works. From the KM plots of the DMGs, GRIN2B is a potential tumor suppressor gene in LUAD, which has been confirmed in some types of cancer, such as diffuse large B-cell lymphoma, 48 gastric cancer, 47 and LUAD. 49 There are 2 main limitations of this study.…”
Section: Discussionmentioning
confidence: 83%
“…To the best of our knowledge, our study is the rst that shows that serum BCA-1 levels are associated with CDI severity. Previous studies have shown association in infected children with helicobacter pylori and in adults with gastric cancer [20]. Other studies reported a poor prognosis in a few types of cancer include gastric cancer and prostate cancer [21,22].…”
Section: Discussionmentioning
confidence: 96%